1952
DOI: 10.1079/bjn19520016
|View full text |Cite
|
Sign up to set email alerts
|

The Nutrition of the Young Ayrshire Calf

Abstract: The purpose of this paper is to describe the histological appearance of tissues from the dystrophic calves reported by Blaxter, Watts & Wood (1952), to compare the dystrophic lesions with those found in naturally occurring muscular dystrophy of cattle (Hjarre & Lilleengen, 1936a, b, Vawter & Records, 1947Slagsvold, 1925), and to relate the chemical composition of the muscle to its histological appearance. METHODSAs described in a previous paper (Blaxter et al. 1952), four experimental groups of calves were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1953
1953
1964
1964

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Broadly speaking, the lesions observed in samples of heart and skeletal muscle were the same as previously found (MacDonald, Blaxter, Watts & Wood, 1952). Agreement between the results of the histological examination and chemical analysis of muscles was good for the skeletal muscles, but only fair for the heart muscle.…”
Section: Histologixal Examinationsupporting
confidence: 66%
See 1 more Smart Citation
“…Broadly speaking, the lesions observed in samples of heart and skeletal muscle were the same as previously found (MacDonald, Blaxter, Watts & Wood, 1952). Agreement between the results of the histological examination and chemical analysis of muscles was good for the skeletal muscles, but only fair for the heart muscle.…”
Section: Histologixal Examinationsupporting
confidence: 66%
“…Previously it had been shown (Blaxter, Watts & Wood, 1952) that muscular dystrophy was associated with a decline in the nitrogen balance and an increase in heat production. The observation that body-weight gain is not appreciably dected would thus appear at variance with these results.…”
Section: Volmentioning
confidence: 99%
“…In some muscle bundles no hyaline fibrils could be seen and yet in adjoining bundles they were present. The hyaline knots and fractures were not considered to be an agonal lesion, since they have not been observed in normal animals that had received adequate vitamin E. This mild lesion was similar to or identical with the early stage of the muscular dystrophy we have already described (MacDonald, Blaxter, Watts & Wood, 1952;Blaxter, Wood & MacDonald, 1953). No abnormalities were ever observed in the left ventricle, all the lesions being found in the skeletal musculature.…”
Section: Histology Of the Musclesmentioning
confidence: 60%
“…After 28 days no difference between the calves of the supplemented and unsupplemented dams was distinguishable. (410,411,412) have produced muscular dystrophy in calves on diets containing cod-liver oil. Piana (407) found that rancid fats produce testicular lesions in male calves.…”
Section: Vitamin Ementioning
confidence: 99%